FAKTOR – FAKTOR YANG MEMPENGARUHI PENINGKATAN KADAR BILIRUBIN PADA BAYI BARU LAHIR DI RUMAH SAKIT HUSADA - ojs, admin; Ernawati, Ernawati; Imelda, Imelda (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2017)
Hiperbilirubin is elevated levels of bilirubin in the extravascular tissue so that the conjunctiva, the skin and the mucous is yellow. The purpose of this study was to find out the factors that influence the levels of bilirubin to increase in bilirubin newborns at Husada Hospital. This research was conducted on 54 respondents, using correlative descriptive design approach survey method. The research results obtained majority factor affecting increased levels of bilirubin in the baby is a factor of low birth weight (<2500gr) 85.7% with a p-value of 0.006 (p <0.005). Babies with low birth weight are more susceptible to Hiperbilirubin, due to their organs are still weak, immature hepatic function or contained in hepatic function disorder such as hypoxia, hypoglycemia, acidosis, and others resulting in increased bilirubin levels.